Factors Associated with the Implementation of Triage by Nurses in the Emergency Room at Dr. Abdul Rivai Berau - Khairil Amin Baso; Wiyadi; Frana Andrianur (Formosa Journal of Applied Sciences, 2023)
Triage is a rescue action in the emergency room which is carried out by grouping patients based on certain criteria. Knowledge, skills and attitudes of ED nurses are needed in clinical decision making so that mistakes do not occur in sorting based on triage so that patient management can be more optimal and directed. This study aims to determine the factors associated with the implementation of triage by nurses in the Emergency Room of RSUD dr. Abdul Rivai Berau. Analytical quantitative research with a cross sectional approach. A sample of 25 people used the total sampling technique. Shows that there is no relationship between training (ρ value 1.000) and years of service (ρ value 0.554) with the implementation of triage. There is a relationship between knowledge (ρ value 0.002), attitude (ρ value 0.004) and skills (ρ value 0.009) with triage.